Pengaruh Gaya Mengajar Guru Terhadap Motivasi Belajar Siswa Di SMP Muhammadiyah 7 Medan - Sifa Maulida; Uswatun Hasanah (Insan Zenius Ilmiah, 2025)
Low student learning motivation is often caused by the application of teacher teaching styles that are not in accordance with the needs and expectations of students. This shows the importance of applying a variety of teaching styles that can help increase student learning motivation. This study aims to determine the effect of variations in teacher teaching styles on student learning motivation at SMP Muhammadiyah 7 Medan. The study used associative quantitative method with a sample of VIII grade students as many as 31 students. Data collection is done through statement sheet instruments that are compiled based on relevant theoretical indicators. The results of the analysis using simple regression test showed a significance value of 0.000 <0.05, with a coefficient value of 0.654. That is, there is a significant positive influence between variations in teacher teaching styles on student learning motivation, with a contribution of 65.4%. Based on the results of the study, it can be concluded that the application of variations in teaching styles by teachers has a significant impact in increasing student learning motivation. Therefore, teachers are expected to continue to develop variations in teaching styles to create a more effective and enjoyable learning atmosphere.